KONTRUKSI NILAI NASIONALISME MELALUI FILM : ANALISIS ISI “FILM WAGE” UNTUK MEDIA PEMBELAJARAN SEJARAH - Roby Firmandil Diharjo; Nining Winarsih; Ainol (UNZAH Genggong, 2021)
This study aims to convey a message to the public. Film is a good medium to transfer cultural and educational values to the audience. This study aims to determine the meaning and values of nationalism in the film wage. This research method uses qualitative research methods with discourse analysis from Norman Fairclough. This research uses data collection techniques in the form of observation, literature study and in-depth interviews. Data analysis techniques in qualitative research are carried out in several stages, namely data reduction, data presentation and conclusion drawing. The result of this research is that the film has a positive meaning. This meaning is what makes us grow the value of nationalism in history lessons. The recommendation given by the researcher in this study is that further research should choose a biopic film that really has a moral message and has deep meaning for the younger generation of Indonesia.Keywords: History Learning Media; Film; Nationalism